Diversification strategies and firm performance in Vietnam: Evidence from parametric and semi‐parametric approaches1. Issue 1 (3rd October 2015) - Santarelli, Enrico; Tran, Hien Thu
Abstract: This paper is based upon the assumption that a firm's profitability is determined by its degree of diversification which is, in turn, strongly related to the antecedent decision to carry out diversification activities. This calls for an empirical approach that permits the joint analysis of the three interrelated and consecutive stages of the overall diversification process: diversification decision, degree of diversification and outcome of diversification. We apply parametric and semi‐parametric approaches to control for sample selection and the endogeneity of the diversification decision in both static and dynamic models. For the analysis, we use the census dataset on the whole firm population in Vietnam, as a representative of transition countries. After controlling for industry fixed‐effects, the empirical evidence from the firm‐level data shows that diversification has a curvilinear effect on profitability: it improves firms' profit up to a point, after which a further increase in diversification is associated with declining performance. This implies that firms should consider optimal levels of product diversification when they expand their product offerings beyond their core business. Other noteworthy findings include the following: (i) the factors that stimulate firms to diversify do not necessarily encourage them to extend their diversification strategy; (ii) firms that are endowed with highly technological resources and innovation investment are likely to successfully exploit diversification as an engine of growth; and (iii) while industry performance does not have a strong influence on the profitability of firms, it impacts their diversification decision as well as the degree of diversification.